2012
DOI: 10.1155/2012/920815
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cone-Beam Computed Tomography and Periapical Radiography in Predicting Treatment Decision for Periapical Lesions: A Clinical Study

Abstract: Objectives. To compare the ability of endodontists to determine the size of apical pathological lesions and select the most appropriate choice of treatment based on lesions' projected image characteristics using 2 D and 3 D images. Study Design. Twenty-four subjects were selected. Radiographic examination of symptomatic study teeth with an intraoral periapical radiograph revealed periapical lesions equal to or greater than 3 mm in the greatest diameter. Cone-beam Computed tomography (CBCT) images were made of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 23 publications
1
36
1
5
Order By: Relevance
“…Presumably, a CBCT examination would not be beneficial to those patients and would thus expose them to deleterious radiation without gain. Balasundaram et al 38 compared CBCT examination with intraoral radiographs and found that for easily diagnosed endodontic cases, CBCT examination does not provide , number of patients; n t , number of examined teeth; T1, was not in the patient's best interest; T2, had no influence in therapy; T3, did not change therapy but increased confidence; T4, contributed to a change in the selected therapy; T5, was the most important factor in the therapy change. birpublications.org…”
Section: Consideration Of the Resultsmentioning
confidence: 99%
“…Presumably, a CBCT examination would not be beneficial to those patients and would thus expose them to deleterious radiation without gain. Balasundaram et al 38 compared CBCT examination with intraoral radiographs and found that for easily diagnosed endodontic cases, CBCT examination does not provide , number of patients; n t , number of examined teeth; T1, was not in the patient's best interest; T2, had no influence in therapy; T3, did not change therapy but increased confidence; T4, contributed to a change in the selected therapy; T5, was the most important factor in the therapy change. birpublications.org…”
Section: Consideration Of the Resultsmentioning
confidence: 99%
“…Estrela et al [14] reported that only progressed periapical lesions were identified correctly by conventional radiography. In contrast, Balasundaram et al [15] reported an only insignificant impact of CBCT diagnosis for the treatment of a respective lesion. Due to the underlying physical principle, all X-ray (XR)-based imaging techniques have limited capabilities in soft tissue characterization and are supposed to be limited in the differentiation between chronic and acute periapical lesions that may have an impact on the treatment strategy.…”
Section: Materials Und Methoden: In Die Studie Wurden 19mentioning
confidence: 93%
“…Thus, there is a need for a noninvasive method to diagnose lesions involving the periapical area. Recently with the advent of imaging modalities such as digital radiography, densitometry methods, computed tomography (CT), magnetic resonance imaging (MRI), ultrasound, and cone beam computed tomography (CBCT), differences in density may permit more accurate preoperative diagnosis [1, 3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…Many subsequent studies since that time have underscored the difficulty of detecting periapical lesions using IOPA radiographs. Therefore, considering some limitations on conventional radiography for detection of periapical bone lesions, advanced imaging methods such as CBCT might add benefits to endodontics and offer a higher quality for the diagnosis, treatment planning, and prognosis [1, 2, 49]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation